Pemodelan Sistem Pemantauan Posisi Kereta Api Berbasis RFID Menggunakan Protokol Message Queue Telemetry Transport (MQTT) - Anggit Surya Gumilang; Rakhmadhany Primananda; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Nowadays trains have become one of the most popular public transportation. The high demand of this transportation certainly will affects increasing the number of trains itself and it's routes. Therefore a system that can facilitate the monitoring of the position of the trains during a trip was required. Indeed PT. Kereta Api Indonesia (Persero) has started applying modern technology in monitoring their trains positions to improve the quality of their services. In monitoring the position of the railway circuit, a GNSS-based monitoring software named LocoTrack has been used before. However, blind spot points and positioning accuracy addressed from GNSS utilization still need to be fixed. This research will discuss about other ways to monitor the position of the trains during a trip that can improve the results of an existing LocoTrack app. This research will propose the use of radio frequency identification (RFID) technology as a marker medium of position and Message Queue Telemetry Transport (MQTT) as data communication protocol. The results showed that the use of RFID as position marker can be done and has very good accuracy. Also the use of the MQTT protocol as a data delivery medium can support lighter and faster delivery.